A dynamic model for the optimization of rotatory feeding devices. (December 2021) - Comand, Nicola; Bottin, Matteo; Rosati, Giulio; Agrawal, Sunil K.
Abstract: Component feeding is an important process in assembly and packaging lines, affecting the throughput. It is therefore important to optimize the feeding process with the aim of reducing the takt time of the production line. In kitting lines, the feeding devices are typically used to create little groups of components, preparing the batches for final grouping into a kit. In the paper, a dynamic model is developed and validated, which describes the interaction of the components to be fed with the blades of a rotating feeding unit. Then, an optimization method is proposed based on the dynamic model using a weighted cost function, which allows to define the shape of the blade according to a set of design objectives. Highlights: The motion of an object on a rotating blade is influenced by the shape of the blade. In perfect rolling condition, acceleration is scaled with respect to sliding motion. The shape of the blade can be optimized using the dynamic model proposed. The feeding phase is improved for devices that handle rolling objects.